Research team - Diana Lê (22639904) (2025)
PI Rachel Anne Tough and research assistant Diana Lê presented the project at the European University Institute's Cultural Heritage Working Group conference in Florence, Italy, May 2023. Videographer Thanh Sơn Nguyễn and photographer Lê Thai Hoàng Nguyễn presented remotely.